Optimization of Acid-Catalyzed Hydrolysis of Water Hyacinth without Delignification - Dedy Anwar; Adonia Christiani Eka Putri; Kenia Ardita Pramesti; Rochim Bakti Cahyono; Irfan Dwidya Prijambada; Wiratni Budhijanto (ASEAN Journal of Chemical Engineering, 2025)
Water hyacinth (Eichhornia crassipes) is a rapidly proliferating invasive aquatic plant causing severe ecological disruptions and economic challenges worldwide. Its uncontrolled spread significantly affects aquatic biodiversity and local livelihoods. Although water hyacinth is rich in cellulose, conventional hydrolysis methods to convert it into valuable bioproducts, such as biofertilizer substrates, often require costly and environmentally harmful pretreatment steps, limiting its broader utilization. This study aimed to optimize acid-catalyzed hydrolysis of water hyacinth into glucose-rich hydrolysate without alkaline pretreatment. Response surface methodology (RSM) was employed to determine optimal conditions using hydrochloric acid (HCl) and sulfuric acid (H2SO4). Optimal hydrolysis conditions were found to be 2.36N concentration, 89.33°C, and 76.94 minutes for HCl, and 1.91N concentration, 100.03°C, and 79.66 minutes for H2SO4. Model validation showed high R² values of 0.82 and 0.95 for HCl and H2SO4, respectively. Subsequent biofertilizer fermentation experiments demonstrated that H2SO4-derived hydrolysate facilitated superior microbial growth compared to HCl, indicating better glucose bioavailability. Hydrolysates from HCl hydrolysis showed higher bacterial toxicity. These findings highlight the potential of optimized acid-catalyzed hydrolysis as an effective, sustainable strategy for converting invasive water hyacinth into glucose-rich substrates for biofertilizer production. This bioprocess-friendly approach not only mitigates environmental impacts but also enhances resource efficiency, contributing significantly to sustainable agricultural practices.